2018
DOI: 10.1063/1.5018058
|View full text |Cite
|
Sign up to set email alerts
|

A study of the asymmetrical distribution of solar activity features on solar and plasma parameters (1967–2016)

Abstract: The impact of asymmetrical distribution of hemispheric sunspot areas (SSAs) on the interplanetary magnetic field, plasma, and solar parameters from 1967 to 2016 has been studied. The N-S asymmetry of solar-plasma activities based on SSAs has a northern dominance during solar cycles 20 and 24. However, it has a tendency to shift to the southern hemisphere in cycles 21, 22, and 23. The solar cycle 23 showed that the sorted southern SSAs days predominated over the northern days by ∼17%. Through the solar cycles 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Furthermore, during the solar cycles 21, 22, and 24, the solar plasma was hotter for days of toward polarity than those of away polarity, whereas during the solar cycles 20 and 23, the solar plasma was cooler for days of toward polarity than those of away polarity. On the other hand, the geomagnetic activity indices (aa, Kp, Ap, and Dst) have been examined on the basis of the asymmetry between the directions of the IMF above and below of the HCS [16]. The study confirmed the existence of significant yearly N-S throughou aa, Ap and Kp asymmetries shifted to the southern solar hemisphere.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Furthermore, during the solar cycles 21, 22, and 24, the solar plasma was hotter for days of toward polarity than those of away polarity, whereas during the solar cycles 20 and 23, the solar plasma was cooler for days of toward polarity than those of away polarity. On the other hand, the geomagnetic activity indices (aa, Kp, Ap, and Dst) have been examined on the basis of the asymmetry between the directions of the IMF above and below of the HCS [16]. The study confirmed the existence of significant yearly N-S throughou aa, Ap and Kp asymmetries shifted to the southern solar hemisphere.…”
Section: Introductionmentioning
confidence: 82%
“…In this section, we have used the daily averages of IMF magnitude (B) and solar-plasma parameters (solar plasma velocity V, plasma density n, plasma temperature T, and plasma dynamic pressure P These interplanetary plasma parameters have been analyzed according to the dominance of hemispheric solar activity indices (SSAs and SSNs) to examine the possible presence of N-S asymmetry. In order to study the relationship between the solar wind parameters and the solar activity indices (SSNs and SSAs), the previous studies of [16,18] indicated that a time-lag (2-yr for T, V, and P as well as 1-yr for n) should be taken into account as well as the data of the interplanetary plasma parameters and the sunspot indices need to be smoothed over 3 years. Data of the daily averages of the interplanetary plasma parameters has been classified into two groups, namely northern (N) and southern (S) groups based on the dominance (sign) of the solar activity in the solar hemisphere of that day.…”
Section: The N-s Asymmetry For the Interplanetary Plasma Parameters According To Hemispheric Distribution Of Ssasmentioning
confidence: 99%